Density fluctuations with fractal order in metallic glasses detected by synchrotron X-ray nano-computed tomography. (15th August 2018) - Huang, B.; Ge, T.P.; Liu, G.L.; Luan, J.H.; He, Q.F.; Yuan, Q.X.; Huang, W.X.; Zhang, K.; Bai, H.Y.; Shek, C.H.; Liu, C.T.; Yang, Y.; et al.
Abstract: We report density fluctuations spanning from nano-to micrometer scale in the three-dimensional (3D) space in metallic glasses (MGs) detected with synchrotron X-ray nano-computed tomography, which decouple with the chemical homogeneity. The MG quenched from fragile supercooled liquid exhibits a more heterogeneous microstructure with a gradient density fluctuation. Severe inhomogeneous deformation rejuvenates the microstructure of the MG with the creation of a large amount of low-density regions, which percolate into shear-band-like layers. Ramified 2.5-dimensional fractal low-density regions exist in all the MGs with the correlation length increasing with microstructural heterogeneity. The formation of the density fluctuations with fractal order in the MGs is discussed based on the percolation of low-density regions and shear transformation zones during the glass transition and deformation processes. Our results directly demonstrate the existence of fractal low-density entropic droplets in MGs affected by fragilities and thermomechanical histories, which could be significant for understanding and controlling the disordered structure of amorphous solids. Graphical abstract: Image 1